Obesity, unhappiness, and The challenge of affluence: theory and evidence - Andrew J. Oswald; Nattavudh Powdthavee (Institute for the Study of Labor (IZA), 2007)
Is affluence a good thing? The book The Challenge of Affluence by Avner Offer (2006) argues that economic prosperity weakens self-control and undermines human well-being. Consistent with a pessimistic view, we show that psychological distress has been rising through time in modern Great Britain. Taking over-eating as an example, our data reveal that half the British population view themselves as overweight, and that happiness and mental health are worse among fatter people in both Britain and Germany. A 10-point move up in body mass index (BMI) is associated in the cross-section with a drop in psychological health of approximately 0.3 GHQ points. Comparisons also matter. For a given level of BMI, we find that people who are educated or who have high income are more likely to view themselves as overweight. We discuss problems of inference and argue that longitudinal data on BMI are needed. We suggest a theory of imitation where utility depends on relative weight in which there can be obesity spirals after only small drops in the price of food.
urn:nbn:de:101:1-2008041009
Keywords: 330; Reichtum; Lebenszufriedenheit; Theorie